(untitled) (Revista INTEREDU11, 2024)
The professional competencies of a teacher of language and literature become remarkable in the teaching activity; the professional development of this teacher is evolutive which requires specific competencies to manage both the long-lasting life professional development and the teaching of discipline. This work analyzes the challenges proposed by the acquisition and development of teaching professional competency within the teaching in language and literature scope. By taking into account the literature review where the way formative programs are carried out to train new teachers, it is observed that the competency-based approach has not been set up in agreement. The results of this research reveal the existence of a gap in the described area. Then, this work accounts for (a) there is no clear conceptualization regarding the understanding of initial training in the scope of humanities, and (b) the competency models where the curriculum designs are based are simply variations or adaptations of the analyzed approaches, are applied in an isolated and/or discretionary way without identifying an organizational axis to indicate how to use each of them.